Investigation of microbiological spoilage and demonstration of the anti-bacterial activity of the major imported fruits within Dhaka Metropolis - Feroz, Farahnaaz; Senjuti, Jessica Das; Tahera, Jannatun; Das, Kamal Kanta; Noor, Rashed (Stamford Journal of Microbiology, 2015)
With a previous observation of the in vitro anti-bacterial traits posed by both local and imported fruit alcoholic extracts, present study further endeavored principally to chalk out such properties of the imported fruit blends without alcoholic extraction. Experiments regarding microbiological load demonstrated the prevalence of huge number of total viable bacteria (~107 cfu/g) as was also observed in the earlier research while the fungal load was nominal. Among the pathogenic bacteria, Pseudomonas spp. was found to be more prevalent, closely followed by staphylococcal proliferation. The study of anti-bacterial activity revealed that guava, apple and malta samples possessed strong anti-bacterial traits while the dragon fruit samples exhibited least activity and the orange samples were found with moderate anti-bacterial activity. On the basis of our earlier results, the findings of the current study thus put forward a comparison among the alcoholic extracts and the crude fruit blends. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22752 Stamford Journal of Microbiology, Vol.4(1) 2014: 1-4